A comparative analysis between field-oriented control and uncontrolled current operation of a brushless DC motor - Uzzaman, Nahid (Kansas State University, 2019)
Field-oriented control (FOC), also known as vector control is a very popular and effective way of driving a Brushless DC (BLDC) motor. However, the BLDC motor can also be run without any current controlling. In this thesis, this method is addressed as uncontrolled current operation, which is simply driving a BLDC motor in the absence of vector control. The characteristics and conditions for effective operation of the uncontrolled current are studied. The thesis discusses and models both vector control and uncontrolled current operation and describes a Simulink simulation building procedure for these two methods. An overall comparison is carried out between these two methods for various aspects, such as commutation accuracy, maximum torque production, handling of external delays, etc. In the analysis, it is seen that the vector control shows a better operating range, but the uncontrolled current shows better stability. The simulation shows that vector control cannot handle external hindrance (such as the computing delay of the controller) very well. On the other hand, the uncontrolled current can handle external delay better. This makes the uncontrolled current method suitable to be used in a microcontroller, as microcontrollers can be slow. Whereas, the vector control will require a very fast computer. As a potential application, the system with the uncontrolled current method is then simulated as laboratory equipment for an introductory control theory course. The model and simulation generated data shows a good match, which indicates uncontrolled current method can be used to build a low-cost introductory control theory laboratory equipment.
Keywords: Control system; Field oriented control; Vector control; Brushless DC motor